Analyzing objects in images for estimating the delamination influence on load carrying capacity of composite laminates - L. M. Durão (2007)
The use of fiber reinforced plastics has increased in the last decades due to their unique properties. Advantages of their use are related with low weight, high strength and stiffness. Drilling of composite plates can be carried out in conventional machinery with some adaptations. However, the presence of typical defects like delamination can affect mechanical properties of produced parts. In this paper delamination influence in bearing stress of drilled hybrid carbon+glass/epoxy quasi-isotropic plates is studied by analyzing objects in images. Conclusions show that damage minimization is an important mean to improve mechanical properties of the joint area of the plate and the appropriateness of the image processing techniques used.